Mekanisma aliran lembapan dalam konkrit keras - Kamarudin Mohd Yusof, (1989)
This paper is a study on the mechanism Of moisture movement in concrete. The influence and effect of severalfactors are discussed. The suitability of a few flow models to the moisture movement in concrete was investigated. Several investigations to be taken into account in the formulation of the moisture flow model in concrete are made